Future market design options for electricity markets with high RES-E: Lessons from the irish single electricity market - Muireann Lynch; Genaro Longoria; John A. Curtis (The Economic and Social Research Institute (ESRI), 2021)
Variable renewable electricity generation presents challenges for traditional power markets. The island of Ireland has high levels of renewable generation by international standards with even higher levels envisaged and so must address these challenges. Market design is informed and constrained by EU policy and progress to date has been mixed. A qualitative review finds that market redesign is advised to address price cannibalisation, reveal consumer preferences for security and protect vulnerable households. Options for market design are presented and recommendations for short and medium term policy action are made.
Keywords: 330; Strommarkt; Erneuerbare Energie; Mechanismus-Design-Theorie; EU-Energiepolitik; Irland